STUDI NARATIF MOTIVASI ORANGTUA MEMILIH LEMBAGA BIMBINGAN BELAJAR ANAK HEBAT UNIT 1418 DI DESA PLUNTURAN, PULUNG, PONOROGO - rega trendy (ROSYADA: Islamic Guidance and Counseling, 2021)
AbstactThis study aims to explore and find out the background of parents enrolling preschool-aged children into Great Children's tutoring, knowing the expectations of parents enrolling preschool-aged children into Great Children's tutoring, knowing the results of children's development after studying at Great Children's tutoring. This research uses qualitative research with descriptive narrative analysis method. The results of this study indicate that the background of parents enrolling their children in great children's tutoring is due to the motivation for achievement needs, the need for self-promotion (exhibition), the need to make others feel good (succorance), the need for order, and the need to balance. (counteraction).Keywords: parental motivation, tutoring, needs